Research into dynamics of setting the threshold and a probability of ignition detection by selfadjusting fire detectors - Pospelov, Boris; Andronov, Vladimir; Rybka Evgenіy; Skliarov, Stanislav (Eastern-European Journal of Enterprise Technologies, 2017)
A general analysis of self-adjustment algorithm of fire detectors for early guaranteed ignition detection was carried out. It was shown that step magnitude in the algorithm of self-adjustment of fire detectors can be a fixed or a selected variable, depending on the level of registered actual data about the factor of ignition of combustible material. Specific features of fire detectors, self-adjusting by ignition, relate to a non-linear nature of the algorithm and conditions for providing guaranteed ignition detection. In this case, for effective self-adjustment of fire detectors, it is expedient to set the initial threshold value by registered actual data in the absence of ignition and to regulate the adaptation step size in a special way. It was shown that the fact of an increase in self-adjusted threshold relative to its original value can be a sign of ignition detection. For probabilistic assessment of the fact of ignition detection, it was proposed to use exponential smoothing of characteristic function, which allows generation of dynamic assessment of probability of ignition detection. A study of dynamics of self-adjusting threshold and probability of ignition detection indicate capability of self-adjusting fire detectors to provide early guaranteed detection of different sources of ignition of flammable materials under conditions unknown in advance